Condensation reactions assisted by acidic hydrogen bonded hydroxyl groups in solid tin(ii)hydroxychloride - Marakatti, Vijaykumar S.; Shanbhag, Ganapati V.; Halgeri, Anand B. (RSC advances, 2013)
Tin(ii)hydroxychloride is reported as a heterogeneous Broensted acid catalyst. Sn(OH)Cl was synthesized by a precipitation method and characterized by XRD, FT-IR, super(1)H MAS NMR, SEM, TG-DTA and N sub(2) sorption. The acidity measurements of tin(ii)hydroxychloride by FT-IR pyridine adsorption and super(1)H MAS NMR showed the presence of Broensted acidity. The Broensted acidity can be attributed to strong hydrogen bonding between the -OH and Cl groups. Sn(OH)Cl showed high activity for important condensation reactions such as the Prins condensation, Claisen-Schmidt condensation and ketalization. The catalytic activity of Sn(OH)Cl was compared with that of SnO, SnO sub(2) and Sn sub(2)(OH) sub(2)O. The catalyst was recycled three times with a negligible decrease in activity.